A novel antiviral peptide against avian influenza virus H9N2. - Yusoff, Khatijah; Omar, Abdul Rahman; Ideris, Aini; Rajik, Mohamed (2008)
The present invention relates to recombinant phages carrying fusion peptides that bind to avian influenza virus (AIV). Such phages are useful as diagnostic reagents to replace anti-AIV antibodies because the phages are capable of competing with the latter antibodies for binding sites on the virus. Synthetic peptides with the sequence CNDFRSKTC, either in linear or cyclic conformations, or fusion phages bearing the above said peptides inhibited AIV propagation in embryonated egg as well as in MDCK cell lines. Therefore they may be used as therapeutic agents to control, to treat and to eradicate bird flu caused by avian influenza virus.